Research on thermal conductivity of compressed pyrophyllite block during diamond synthesis at HT/HP - Deng Wenli; Deng Fuming; Yang Xuefeng; Ma Xiandong; Xu Chenyang; Xie Yajuan (矿业科学学报, 2018)
For the in situ testing problems of thermal conductivity of pyrophyllite at HT/HP，in the paper the thermal conductivity of compressed pyrophyllite block before and after diamond synthesis at HT/HP were tested by using the comprehensive property measurement system PPMS and laser conductometer LFA427.The results showed that the thermal conductivity of compressed pyrophyllite before diamond synthesis was about 6.45 W/(m·K)，which was 2.77 W/(m·k) after diamond synthesis at HT/HP.It was found that the thermal conductivity in the intermediate layer of pyrophyllite block was the largest，followed by the inner，and the outer layer of pyrophyllite block was the minimum.XRD analysis results showed that the crystal plane distance of pyrophyllite block was expanded instead of compressed after HT/HP process with the biggest expansion ratio at the intermediate layer，then the inner layer and the minimum in the outer layer of the block.Therefore it seem that the decrease of the thermal conductivity was obviously related with interplanar spacing expansion of pyrophyllite after HT/HP process.According to the theoretical thermal conductivity model of the spring oscillator，the decrease of the thermal conductivity of the pyrophyllite block after HT/HP process was explained，and the thermal conductivity of compressed pyrophyllite block under HT/HP of diamond synthesis was deduced to be about 10.13 W/(m·K).